Research Handbook on International Law and Terrorism - Saul, Ben.; Saul, Ben (UK; USA: Edward Elgar, 2021)
"This newly revised and updated second edition provides a comprehensive overview of international counter-terrorism law and practice. Brand new and revised chapters provide critical commentary on the law from leading scholars and practitioners in the field, including new topics for this edition such as foreign terrorist fighters, the nexus between organized crime and terrorism, and the prevention of violent extremism."
Includes bibliographical references and index.
Keywords: Terrorism (International law)